Majapahit Cultural Center di Mojokerto dengan Penerapan Eco-Cultural Design - Ivan Wahyu Oktsandy; Ema Yunita Titisari (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2024)
Mojokerto is known for its numerous historical and cultural attraction. However, the public's interest in cultural tourism is low in compared to other types of tourism. Mojokerto contains a wide range of cultural heritages, from oral traditions to performing arts, yet there are no cultural promotion artifacts in the Mojokerto region. Furthermore, green spaces account for less than 20% of the overall area, lowering the community's quality of life and negatively affecting the ecosystem. Majapahit Cultural Center's mission is to create a space for the community to grow and preserve culture, to become a cultural and historical tourist attraction, to improve the quality of life, and to protect the environment. The design of Majapahit Cultural Center uses rationalism method with precedent study. The precedent that becomes a reference is the Singkawang Cultural Center located in West Kalimantan. The design employs the Eco-Cultural Design method, which has seven key components. The design resulted in a cultural center building with traditional Majapahit local ornamentation and several amenities to meet cultural development and preservation objectives. Not only that, Majapahit Cultural Center applies various principles of ecological architecture as an effort to preserve the environment.